Evaluasi Atas Sistem Produksi Dalam Hubungannya Dengan Efektivitas Operasi Studi Kasus pada PT. Goodyear Indonesia, Tbk - Edison, Edison; Yuniar, Yuniar (Jurnal Ilmiah Ranggagading (JIR), 2009)
The goal of this research is to evaluate production system applied by manufacture company in producing tires to reach effective operation. This research used descriptive qualitative data. The result o the evaluation shows that PT Goodyear Indonesia Tbk. has determined standard cost in carryng out the project effectively. The effectiveness of work accomplishment depends on how the work accomplishment has met a demand by yielding tires of good quality and sucure produced by high technology for drivers and passengers in Indonesia. Key words: Production system Operational effectiveness